1964
DOI: 10.1530/jrf.0.0070267
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogenic and Anti-Oestrogenic Activity of Androgens in the Ewe

Abstract: Seventy-two spayed crossbred ewes were used in a series of five successive tests, at intervals of 15 days, in a study of the actions and interactions of androgen, oestrogen and progesterone on behavioural and vaginal oestrous responses.Androgen and oestrogen were additive in their action (128 vs. 62 services; P<0\m=.\001) on behavioural response, but androgen almost completely inhibited the expected vaginal response to oestrogen.There was a significant linear decline in behavioural sensitivity from test to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The augmentation of oestrogen-induced behavioural oestrus by androstenedione is similar to that by testosterone, in that vaginal oestrus is also inhibited (Lindsay & Robinson, 1964). Its behavioural effect may be due to a direct action on reacting neurones or to pro-oestrogenic activity after conversion to oestrogen or testosterone.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The augmentation of oestrogen-induced behavioural oestrus by androstenedione is similar to that by testosterone, in that vaginal oestrus is also inhibited (Lindsay & Robinson, 1964). Its behavioural effect may be due to a direct action on reacting neurones or to pro-oestrogenic activity after conversion to oestrogen or testosterone.…”
Section: Resultsmentioning
confidence: 75%
“…Testosterone given with oestrogen to progesterone-primed ovariectomized ewes has a dual action (Lindsay & Robinson, 1964). Oestrogen-induced behavioural oestrus is augmented by the testosterone but the normal vaginal smear response (Robinson & Moore, 1956) is virtually eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…Current thinking is that androgen can be aromatized to oestrogen but, if so, only the neural receptor sites have this capacity; peripheral sites do not. Interestingly, further studies showed that oestrogen and androgen were additive in their effect on behaviour but antagonistic on the vaginal response (Lindsay & Robinson, 1961a& Robinson, , 1964).…”
Section: Eps Ementioning
confidence: 99%
“…First of all, the progesterone-oestrogen interaction on oestrous behaviour and vaginal changes had been worked out in detail (see Robinson, 1959). Secondly, it had been shown that the behavioural and peripheral components of oestrus were not necessarily dependent (Lindsay & Robinson, 1961a& Robinson, , 1964. Thirdly, the myth of rams detecting ewes in oestrus had been exploded; oestrous ewes either find their mates or permit themselves to be found (Inkster, 1957; Lindsay & Robinson, 1961b).…”
Section: Eps Ementioning
confidence: 99%